Intertarsal and Tarsometatarsal Arthrodesis Using a Plantar Approach - Wilke, V. L.; Robinson, T. M.; Dueland, R. T. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
The exposure and convenience of a plantar approach combined with the use of various plates for intertarsal and tarso-metatarsal arthrodesis is reported in four limbs. The approach was straight-forward with good exposure and the design of the new carpal arthrodesis plate uniquely accommodated the plantar tarsometatarsal anatomy.This report in dogs concerns one case of bilateral auto-immune proximal intertarsal subluxation (talocalcaneal-centroquartal), one case of traumatic intertarso-metatarsal luxation and one case of traumatic tarsometatarsal subluxation/fracture. All were treated by arthrodesis using a plantar approach with a plate as primary fixation.
Keywords: Intertarsal arthrodesis; tarsometatarsal arthrodesis; plantar approach; carpal arthrodesis plate; tarsal arthrodesis